IL-25 dampens the growth of human germinal center-derived B-cell non Hodgkin Lymphoma by curtailing neoangiogenesis - Ferretti, Elisa (Oncoimmunology, 2017)
Interleukin (IL)-25, a member of the IL-17 cytokine superfamily, is produced by immune and non-immune cells and exerts type 2 pro-inflammatory effects in vitro and in vivo. The IL-25 receptor(R) is composed of the IL-17RA/IL-17RB subunits. Previous work showed that germinal centre (GC)-derived B-cell non Hodgkin lymphomas (B-NHL) expressed IL-17AR, formed by IL-17RA and IL-17RC subunits, and IL-17A/IL-17AR axis promoted B-NHL growth by stimulating neoangiogenesis. Here, we have investigated expression and function of IL-25/IL-25R axis in lymph nodes from human GC-derived B-NHL, i.e. Follicular Lymphoma (FL,10 cases), Diffuse Large B Cell Lymphoma (6 cases) and Burkitt Lymphoma (3 cases). Tumor cells expressed IL-25R and IL-25 that was detected also in non-malignant cells by flow cytometry. Immunohistochemical studies confirmed expression of IL-25R and IL-25 in FL cells, and highlighted IL-25 expression in bystander elements of the FL microenvironment. IL-25 i) up-regulated phosphorylation of NFkBp65, STAT-1 and JNK in B-NHL cells; ii) inhibited in vitro proliferation of the latter cells; iii) exerted anti-tumor activity in two in vivo B-NHL models by dampening expression of pro-angiogenic molecules as VEGF-C, CXCL6 and ANGPT3. In conclusion, IL-25, that is intrinsically pro-angiogenic, inhibits B-NHL growth by reprogramming the angiogenic phenotype of B-NHL cells.